1996
DOI: 10.1007/bf02285162
|View full text |Cite
|
Sign up to set email alerts
|

Additive effect of nitric oxide and prostaglandin-E2 synthesis inhibitors in endotoxin-induced uveitis in the rabbit

Abstract: The involvement of nitric oxide (NO) and prostaglandin E2 (PGE2) was investigated in a model of intraocular inflammation induced by intravitreal injection of endotoxin (lipopolysaccharide, LPS, 10 ng) in rabbits. The severity of uveitis, the myeloperoxidase (MPO) activity in iris-ciliary body, and the protein concentration in aqueous humor were determined. Nitric oxide synthase (NOS) and cyclooxygenase (COX) activities were assessed respectively by nitrite and PGE2 levels in aqueous humor. Treatment with inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 26 publications
1
47
0
Order By: Relevance
“…The expression of the inducible enzymes, responsible for their synthesis (COX-2 and iNOS respectively), is also controlled by NF-κB. Bellot et al (Bellot et al, 1996) reported that PGE2 and NO have an additive effect in EIU in rabbits and that inhibition of both pathways would improve the therapeutic management of uveitis. Therefore our data suggest that the suppressed ocular inflammation can be attributed in part to the down-regulation of these mediators by captopril.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of the inducible enzymes, responsible for their synthesis (COX-2 and iNOS respectively), is also controlled by NF-κB. Bellot et al (Bellot et al, 1996) reported that PGE2 and NO have an additive effect in EIU in rabbits and that inhibition of both pathways would improve the therapeutic management of uveitis. Therefore our data suggest that the suppressed ocular inflammation can be attributed in part to the down-regulation of these mediators by captopril.…”
Section: Discussionmentioning
confidence: 99%
“…LPS triggers the secretion of a variety of inflammatory mediators, such as TNF-α (Tracey and Cerami, 1994), prostaglandin E2 (PGE2) (Bellot et al, 1996); Murakami et al, 2000), MCP-1 (Tuaillon et al, 2002), as well as the generation of ROS and excessive amounts of nitric oxide (NO) (Nathan and Xie, 1994), which all contribute to the pathophysiology of septic shock. The transcription of a significant number of these inflammatory mediators is triggered by the intracellular activation of NF-κB.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that uveitis is one of the main causes of eye morbidity and loss of visual functions, the complexity of the biochemical and immune mechanisms involved in its generation and development remain unknown. Several lines of evidence support that the disease is due to damage generated by infiltrated leukocytes, which release cytokines 1,2 and other inflammatory chemical mediators, like arachidonic acid metabolites, 3 reactive oxygen species, 4,5 and nitric oxide (NO), 6 among many others. Arachidonic acid metabolites regulate vascular permeability, chemotaxis, and contribute to uveitis amplification.…”
Section: Uveitis Is a Common Ophthalmic Disorder That Can Be Induced mentioning
confidence: 99%
“…LPS enhances the expression of various inflammatory mediators, such as tumor necrosis factor (TNF)-␣, 1 interleukin (IL)-6, 1,2 prostaglandin E2, 3 and NO, 6,18 all of which contribute to the development of the disease. Several lines of evidence support that EIU mimics central features of human uveitis, such as the breakdown of the BOB, and infiltration of leukocytes.…”
Section: Uveitis Is a Common Ophthalmic Disorder That Can Be Induced mentioning
confidence: 99%
See 1 more Smart Citation